2016
DOI: 10.1159/000447922
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ERK1/2 Signaling Pathway is Involved in Melatonin's Antiproliferative Effect on Human MG-63 Osteosarcoma Cells

Abstract: Background: In a previous study, we found that melatonin inhibits MG-63 osteosarcoma cell proliferation; however, the underlying mechanisms remain elusive. Mitogen-activated protein kinase (MAPK) and Akt signaling pathways play key roles in the anticancer effects of melatonin. Aims: The present study investigated whether MAPK and Akt signaling pathways are involved in melatonin's antiproliferative actions on the human MG-63 osteosarcoma cells. Methods/Results: Western blot analysis confirmed that melatonin sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 43 publications
1
46
0
Order By: Relevance
“…Considering other studies showing that melatonin inhibition of cancer cell growth involves mitogen-activated kinases and AKT signaling, Liu et al [268] examined changes in these signaling pathways in an attempt to determine if they also relate to the mechanisms by which melatonin interferes with the proliferation of osteosarcoma cells. In human MG-63 osteosarcoma cells, melatonin significantly inhibited the phophoactivation of ERK1/2 but was without effect on either p38, JNK or AKT.…”
Section: Melatonin and Cancer Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering other studies showing that melatonin inhibition of cancer cell growth involves mitogen-activated kinases and AKT signaling, Liu et al [268] examined changes in these signaling pathways in an attempt to determine if they also relate to the mechanisms by which melatonin interferes with the proliferation of osteosarcoma cells. In human MG-63 osteosarcoma cells, melatonin significantly inhibited the phophoactivation of ERK1/2 but was without effect on either p38, JNK or AKT.…”
Section: Melatonin and Cancer Progressionmentioning
confidence: 99%
“…Likewise, when MG-63 cells were incubated with a combination of melatonin and PD98059, it highly effectively blocked ERK1/2 activation. Thus, ERK1/2 inhibition is likely involved in the process by which melatonin arrests MG-63 osteosarcoma cells in the G1 and G2/M phases of the cell cycle [268]. In contrast, since p38, JNK and AKT were not changed by melatonin treatment, it was concluded these pathways are not involved.…”
Section: Melatonin and Cancer Progressionmentioning
confidence: 99%
“…Numerous studies have documented that melatonin displays several anticancer effects, by pleiotropically acting upon different targets, including ERK activation . Indeed, melatonin can efficiently mitigate and even suppress migration and invasiveness in different cancer types, such as nasopharyngeal, renal, gastrointestinal, and breast tumors, probably involving a wide range of different actions, including CSK remodeling …”
Section: Introductionmentioning
confidence: 99%
“…In a gastric cancer cell line it was already shown that proapoptotic effect of melatonin could be due to activation of a Caspase-dependent pathway and inhibition of the nuclear translocation of NF-κB p65, two processes that are regulated by p38 and c-Jun N-terminal kinase (JNK) [18]. Nevertheless, in human MG-63 osteosarcoma cells melatonin´s antiproliferative action was mediated by inhibition of the extracellular signal-regulated kinase (ERK1/2) signalling pathway rather than the p38, JNK, or Akt pathways [19]. However, the precise molecular mechanisms of melatonin action in cancer cells are still under investigation.…”
Section: Introductionmentioning
confidence: 99%